Social Adaptation and Potential for the Development of Fisheries Empowerment in Barrang Lompo Island Indonesia - Abdullah, Suparman; Genda, Arsyad; Djibe, Sultan; Radjab, Manshur; Sabiq, Andi Muh. (International Journal of Psychosocial Rehabilitation, 2020)
Fishermen are always positioned as a low-level, marginalized community. They are also considered to have various limitations and helplessness even weak social adaptability. However, for the case of sea cucumber fishermen the workers are slightly different. They actually have sides of adaptability and potential empowerment. This study aims to identify and describe the strength of social adaptation and the potential empowerment of sea cucumber fishermen labor communities on the Barrang Lompo Island of Makassar. The research approach method used is qualitative with the basis of case studies, namely a comprehensive, in-depth and specific study. Informants as many as 7 formal and informal community leaders were determined purposively. The method of data collection is in depth interview, observation and literature review. Data were analyzed in stages which included data collection, data verification, data exposure and analysis. The results of the study showed that there were identified and illustrated several potential empowerments and social adaptations possessed by the BECHZE-DE-MER fishing workers on Barrang Lompo Island which included: First; The existence of awareness and expectations, which are interpreted as enthusiasm, work ethic and motivation to improve their socio-economic status, second; The existence of participation and activity is interpreted as existence in social life which is manifested in the form of productive activities and actions, third; The existence of institutions as a means of adaptation is interpreted as part of membership that is used for facilities in meeting life's needs and fourth; Social accessibility and adaptation are intended as behaviors and actions to build relationships that are horizontal and vertical in nature as social processes and dynamics